2014
DOI: 10.1159/000365449
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Relevance of Aberrant DNA Methylation in G1 and G2 Pancreatic Neuroendocrine Tumors

Abstract: Background/Aims: The occurrence and clinical relevance of DNA hypermethylation and global hypomethylation in pancreatic neuroendocrine tumours (PanNETs) are still unknown. We evaluated the frequency of both epigenetic alterations in PanNETs to assess the relationship between methylation profiles and chromosomal instability, tumour phenotypes and prognosis. Methods: In a well-characterized series of 56 sporadic G1 and G2 PanNETs, methylation-sensitive multiple ligation-dependent probe amplification was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 45 publications
3
56
0
1
Order By: Relevance
“…LINE1 hypomethylation significantly correlated with poor prognosis and advanced tumour stage in PanNET (Stefanoli et al 2014). Interestingly, in the same study, the authors found that DAPK1, TIMP3, PAX5, HIC1, CADM1, PYCARD, ESR1, VHL, RARB and WT1 promoters were significantly hyper-methylated in late-stage tumours and in tumours with poor prognosis (Stefanoli et al 2014). However, the majority of the tumours did not show simultaneous global hypomethylation and CpG hypermethylation suggesting that in PanNET the two mechanisms are independent.…”
Section: Pancreatic Netmentioning
confidence: 94%
“…LINE1 hypomethylation significantly correlated with poor prognosis and advanced tumour stage in PanNET (Stefanoli et al 2014). Interestingly, in the same study, the authors found that DAPK1, TIMP3, PAX5, HIC1, CADM1, PYCARD, ESR1, VHL, RARB and WT1 promoters were significantly hyper-methylated in late-stage tumours and in tumours with poor prognosis (Stefanoli et al 2014). However, the majority of the tumours did not show simultaneous global hypomethylation and CpG hypermethylation suggesting that in PanNET the two mechanisms are independent.…”
Section: Pancreatic Netmentioning
confidence: 94%
“…Aberrant methylation of CpG islands is a well-known mechanism associated with the silencing of cancer-related genes in several cancers including pancreatic adenocarcinomas (58, 59) and PanNETs (60). In the literature, there is only one study, which, analyzing the promoter methylation status of 34 tumor suppressor genes, evaluated the methylation profile of ACCs (37).…”
Section: Acinar Cell Carcinoma In Adultsmentioning
confidence: 99%
“…In general, ACCs showed low levels of hypermethylation and no tumors characterized by concerted hypermethylation at multiple loci were identified among 55 ACC/MANECs investigated. Consequently, the so-called “CpG island methylator phenotype (CIMP)” described not only in colorectal cancers but also in pancreatic ductal adenocarcinomas and PanNETs (60, 61) seems not to be present in pancreatic ACCs. However, some genes, including RASSF1 and APC , frequently were found to be methylated.…”
Section: Acinar Cell Carcinoma In Adultsmentioning
confidence: 99%
“…The recurrence rate postresection in patients with PanNENs varies markedly in different series and, as outlined in a previous paragraph, it is affected by the type of PanNEN included (insulinomas, the most frequent F-PanNEN, have a very low recurrence rate) [61], the tumor grade, the tumor stage, and the pathologic features other than grade/differentiation of the tumors, such as degree of invasion [20, 21, 24-31, 33-36]. In addition, other molecular features of PanNENs have been shown to correlate with tumor aggressiveness/recurrence, including ATRX/DAXX/telomere changes and changes in other chromatin remodeling genes [62], miRNA/mRNA transcriptome profiles [63], methylation status [64], and a number of other alterations [65] (Table 2). Each of the radiologic features discussed above in Possible Unmet Needs Protocol 1 could also be correlated with tumor aggressiveness/recurrence either from preoperative/pretreatment studies or residual tumor.…”
Section: Unmet Needs: Potential Specific Protocol Topicsmentioning
confidence: 99%